Optimization of Gula Semut Merah Innovation Based on Palm Sap in Supporting the Local Economy of Way Kalam Village, South Lampung - Wijaya, Acum; Aulia, Azizah Nur; Setiowati, Dwi Ayu; Chairunnisa, Chairunnisa; Nugroho, Yugo Dwi; Putri, Risa Haruman; Nuryana, Risma Pitriani; Koironi, Ani (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Community service is an activity aimed at contributing to society without expecting financial compensation. Students participating in the Community Service Program (KKN) have carried out such activities in Way Kalam Village, Penengahan District, by utilizing the natural resources available in the area. The main focus of the program was the processing of palm sap into palm sugar, characterized by its unique flavor and fine-grain texture. During the implementation, the local community was introduced to an innovative method of processing palm sap into palm sugar. The community’s response was highly positive, as reflected in their enthusiasm and active participation. Moreover, they came to understand that the production process is relatively simple and holds promising market potential. This community service initiative has had a meaningful impact, not only by enhancing knowledge about alternative business opportunities but also by contributing to the economic improvement of the local population.